Children and adolescents’ health-related quality of life in relation to eczema, asthma and hay fever: results from a population-based cross-sectional study - Matterne, Uwe; Schmitt, Jochen; Diepgen, Thomas L.; Apfelbacher, Christian (Quality of life research, 2011)
Purpose: Several studies have looked at the relationship between childhood atopic disease and health-related quality of life (HRQoL), but existing research is limited by selected populations, small samples or lack to consider each of the three atopic conditions simultaneously. Methods: Impact of 4-week and 12-month occurrences of the three conditions on HRQoL were analysed by the use of complex sample general linear models alone and adjusted for the other atopic conditions, sociodemographics and mental health in a population-based sample (n = 6,518) of children and adolescents aged 11–17. Results: In univariate analyses, total HRQoL was significantly impacted by eczema and hay fever but not asthma with stronger effects for 4-week occurrence. In multivariate analyses, 12-month occurrence of hay fever and 4-week occurrence of eczema and hay fever significantly impacted on total HRQoL. Although most of the variance in HRQoL was explained by mental health, independent effects of the atopic conditions remained. Conclusion: Atopic conditions impact HRQoL over and above mental health. When analysing the relationship between atopic conditions and HRQoL, it is important to consider more immediate versus less immediate effects of the conditions. Extent of impairment and the domains affected appear to vary when different time intervals are used.
Gesehen am 12.08.2022